Government Internal Control System (SPIP), Utilization of Information Technology and The Role of Government Internal Supervisory Apparatus (APIP) on The Quality of Local Government Financial Reports - Angela Heinrich; Agung Nur Probohudono (Journal of Current Studies in SDGs, 2027)
Abstract..This study aims to determine the effect of the Government Internal Control System (SPIP), the use of information technology and the role of government Internal Supervisory Apparatus (APIP) on the quality of financial reports in the Kaimana Regency Regional Government. The total respondents were 119 people from 38 Regional Apparatus Organizations in Kaimana Regency consisting of OPD leaders, Head of the finance subdivision, treasurer and APIP / Internal Auditor. The research method used multiple regression analysis with SPSS software. The results showed that the Government Internal Control System (SPIP), the use of information technology, and the role of government Internal Supervisory Apparatus (APIP) had a positive and significant effect on the quality of financial reports in the Kaimana Regency Local Government.